2017
DOI: 10.4172/2329-6925.1000325
|View full text |Cite
|
Sign up to set email alerts
|

Duplex Guided Foam Sclerotherapy Versus Surgery in Management of Primary Varicose Veins

Abstract: Backgroundː Varicose veins is a major problem among adult population. It has a major effect on life quality as well as healthcare system resources, we aim in this study to compare ultrasound guided foam sclerotherapy (UGFS) with surgery in management of primary varicose veins patients and to measure patients' satisfaction with either modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In the study of Gamal WM et al, most common complication was pain at injection site (12.0%), hyperpigmentation (10.0%), thrombophlebitis (10.0%), telangiectasia matting (8.0%), headache (6.0%), DVT (2.0%) and pulmonary embolism (2.0%). 9 Madhu et al observed pain at the injection site in 11.5% patients, thrombophlebitis in 21.0% cases. 5 Hyperpigmentation was seen in 17% cases which was reduced to 3.0%, with persisting hyperpigmentation on the calf.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In the study of Gamal WM et al, most common complication was pain at injection site (12.0%), hyperpigmentation (10.0%), thrombophlebitis (10.0%), telangiectasia matting (8.0%), headache (6.0%), DVT (2.0%) and pulmonary embolism (2.0%). 9 Madhu et al observed pain at the injection site in 11.5% patients, thrombophlebitis in 21.0% cases. 5 Hyperpigmentation was seen in 17% cases which was reduced to 3.0%, with persisting hyperpigmentation on the calf.…”
Section: Resultsmentioning
confidence: 97%
“…It was concluded that foam sclerotherapy was as effective as surgery. 9 However, Brittenden et al documented that the frequency of completely successful ablation of great saphenous veins was significantly higher among participants who were randomly assigned to surgery (84.4%) or laser treatment (83.0%) than among those assigned to foam treatment (54.6%, p<0.001 for both comparisons). 32 The incidence of bruising with saphneous venous stripping was found to be 25-30% reported in different other studies.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the study of Gamal et al [23] in foam group, 92% of patient achieve total occlusion, 2% partial recanalization without reflux, 4% partial recanalization with reflux and 2% total recanalization; 3 patients received another session of UGFS and 4 th one had been satisfied with results and refused to take another session. In their surgery group, 100% achieve total occlusion at 1 month follow up.…”
Section: Discussionmentioning
confidence: 97%
“…total occlusion of great saphenous vein (GSV), recurrence rate and patient satisfaction were almost similar in both the groups. The author used the data to validate that UGFS is as efficient as the surgical treatment method and can be used to replace the conventional surgical interventions if and when required [2].…”
mentioning
confidence: 99%